Utilization of the Growth Chart module in Increasing Mother's Knowledge to Monitor the Grow up of Toddlers - Agus Hendra Al Rahmad; Iskandar Iskandar; T. Khairul Fadjri; Abdul Hadi (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
The lack of knowledge of mothers under five in using and reading the Growth Chart affects the low community participation and visits by mothers to Integrated Healthcare Center and monitoring toddlers' growth. Poor knowledge from mothers allows toddlers not to be monitored for nutritional status. The purpose of the study was to increase the knowledge of mothers of toddlers about monitoring the grow up of toddlers. The study used a quasi-experimental design conducted on 50 mothers of children under five in the Banda Aceh City District. The study was conducted from August – September 2020. Data collection was interviewed using a questionnaire related to identity and knowledge using strict health procedures. The training is conducted online (zoom media) and offline. The data is processed in stages: editing, coding, tabulating, and cleaning—statistical analysis using T-test at 95% CI. The study results show that the growth module training for toddlers affects increasing knowledge by 15.0% or has a mean difference of 3,5 (95% CI: 1,17 – 4,19 with a p-value = 0,002 ( p < 0,05). In conclusion, the growth chart module increases mothers of toddlers' knowledge about monitoring their toddlers' growth. In addition, training on the use of the growth chart module has proven effective in increasing mother knowledge to monitor toddlers' growth.